Synthesis and curing studies of PPG based telechelic urethane methacrylic macromonomers - Asha, S. K.; Thirumal, M.; Kavitha, A.; Pillai, C.K.S. (European Polymer Journal, 2005)
A New class of telechelic urethane methacrylic (TUMA) macromonomers were synthesized by a two-step condensation of 1, 6-hexamethylenediisocyanate (HMDI) with polypropylene glycol (PPG) of various molecular weights and capped with hydroxyl ethyl methacrylate (HEMA). A model compound based on diethylene glycol (DEG)—M-1 was synthesized as a low molecular weight analogue. Another model compound—M-2 was also synthesized by direct coupling of two equivalents of HEMA with HMDI. The structure of the telechelic urethanes were confirmed by 1H, 13C NMR and FTIR spectroscopy. Photopolymerization of these telechelic systems was investigated using 2,2-diethoxy acetophenone as the photoinitiator at 5 wt.%. Trihydroxymethylpropane trimethacrylate (30 parts), PPG diacrylates (25 parts), ethylhexyl acrylate (20 parts) were mixed with the various telechelic urethane methacrylates (25 parts) for curing studies. The kinetics of the curing was monitored by following the disappearance of the methacrylic double bonds at 1628 cm−1 using IR spectroscopy. TUMAPPG-425 had the fastest cure rate among the telechelic urethane methacrylates. This could be accounted for by hydrogen bonding pre-association in these systems. The thermal properties of the cured films were studied using TGA measurements. The cured films of the neat resin had a lower 50 wt.% loss temperature compared with that of the same resin in the formulation.